2008
DOI: 10.37236/731
|View full text |Cite
|
Sign up to set email alerts
|

Osculating Paths and Oscillating Tableaux

Abstract: The combinatorics of certain osculating lattice paths is studied, and a relationship with oscillating tableaux is obtained. More specifically, the paths being considered have fixed start and end points on respectively the lower and right boundaries of a rectangle in the square lattice, each path can take only unit steps rightwards or upwards, and two different paths are permitted to share lattice points, but not to cross or share lattice edges. Such paths correspond to configurations of the six-vertex model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…ASMs with a fixed number of generalized inversions. Expressions for the coefficients of x p in Z n (x, 1), i.e., for the number of n × n ASMs with p generalized inversions, can be obtained using a result of Behrend [15,Cor. 14], and are given by Behrend (1, y), an expression for the coefficient of y m , i.e., for the number of n × n ASMs with m −1s, has been obtained by Cori, Duchon and Le Gac [53,108] , are bijections between ASM(n) and sets of monotone (or Gog) triangles with bottom row 1, .…”
Section: 9mentioning
confidence: 99%
“…ASMs with a fixed number of generalized inversions. Expressions for the coefficients of x p in Z n (x, 1), i.e., for the number of n × n ASMs with p generalized inversions, can be obtained using a result of Behrend [15,Cor. 14], and are given by Behrend (1, y), an expression for the coefficient of y m , i.e., for the number of n × n ASMs with m −1s, has been obtained by Cori, Duchon and Le Gac [53,108] , are bijections between ASM(n) and sets of monotone (or Gog) triangles with bottom row 1, .…”
Section: 9mentioning
confidence: 99%
“…where the terms are written in an order which corresponds to that used in (5) and (6). It follows easily from the definitions of ASMs and DPPs that the generating functions satisfy…”
Section: Preliminariesmentioning
confidence: 99%
“…By using a bijection between ASMs and certain sets of osculating lattice paths, a bijection between DPPs and certain sets of nonintersecting lattice paths, and a result of Behrend [5,Cor. 14], which itself follows from a bijection [5,Thm. 13] between certain sets of paths and certain generalized oscillating tableaux, it can be shown that…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen, using (4) and (9), that a spin r/2 vertex model configuration corresponds to a semimagic square with line sum r if and only if each of its vertex…”
Section: · · ·mentioning
confidence: 99%